(untitled) (ESMAT Magazine, 2025)
This study was carried out as part of the Postgraduate Programme in Society and the Border (PPGSOF) at the Federal University of Roraima (UFRR). This research focused on analyzing obstetric violence experienced by pregnant women, parturients and mothers in the city of Boa Vista - RR. The methodology used was qualitative, descriptive and bibliographical, based on an intersectional feminist epistemology, Gender and History. The general objective was to analyze obstetric violence in the state of Roraima caused by non- compliance with Women's Fundamental Rights, addressing the situation at the Nossa Senhora de Nazareth Maternity Hospital, which, at the time of the research, was operating in a temporary structure made up of tarpaulins and tents. The specific objectives included presenting the case of the tarpaulin/tent maternity hospital in Boa Vista/RR and conceptualizing Obstetric Violence with a focus on gender-based violence. The research sought to investigate the causes and forms of obstetric violence, promoting debate in the medical and legal spheres on the formulation of preventive standards and civil, criminal and administrative liability. It also correlated the understanding of obstetric violence and power relations, considering gender inequality in the context of the Nossa Senhora de Nazareth maternity hospital. The study emphasized respect for women's rights, assessing the forms of abuse of power, since in some cases health professionals used their authority to impose invasive or unnecessary practices, disregarding women's wishes and needs. In this respect, the research highlighted the influence of patriarchal structure and pointed to the need for an in- depth study on the subject. It also included an investigation into the need for humanization in obstetric care, considering that this can be marked by a lack of empathy and welcome for women, generating fear, insecurity and trauma. The results obtained during the research were considered fundamental for the construction of effective public policies that safeguard the fundamental rights of women in Roraima and guarantee access to dignified and adequate health care. The preliminary results indicate the existence of obstetric violence against women in the state of Roraima.